The Effect of Implicit–Explicit Followership Congruence on Benevolent Leadership: Evidence from Chinese Family Firms - Wang, Xiao; Peng, Jian (Frontiers in Psychology, 2016)
Benevolent leadership, a traditional Chinese leadership style generated under the influence of Confucianism, has been under growing discussion since its proposal. However, existing research has focused mainly on the consequences of benevolent leadership, and research probing into its antecedents is scarce. To fill such research gap, the current study aims to explore the effect of the congruence between implicit positive followership prototype (PFP) and explicit positive followership trait (PFT) on benevolent leadership. Polynomial regression combined with the response surface methodology was used to test the hypotheses herein. The results, based on a sample of 241 leader-follower dyads from four companies in China, indicated the following: (1) benevolent leadership is higher when leader PFP is congruent with follower PFT than when they are incongruent; (2) in cases of congruence, benevolent leadership is higher when leader PFP and follower PFT are both high rather than low. (3) In the case of incongruence, there is no significant difference for the level of benevolent leadership in two scenarios: "low leader PFP - high follower PFT" and "high leader PFP - low follower PFT ".